Legal Framework of Cooperation of Russia and the United States in the Bering Strait Region - Elena V. Norkina (Московский журнал международного права, 2016)
The concept of «the Bering Strait region» is a relatively new for the science of international law. Despite this international cooperation in this region is carried out. The article considers the existing agreements concerning the Bering Strait region that were signed by Russia and the United States. The agreements relate to the maritime border between Russia and the United States; cooperation in combating pollution in the Bering and Chukchi seas in emergency situations; conservation and management of the Alaska-Chukotka Polar Bear Population; cooperation to prevent, deter and eliminate illegal, unreported and unregulated fishing; mutual visits by inhabitants of the Bering Straits region; the Bering Strait Regional Commission; scientific and technical cooperation. Based on the analysis of existing bilateral agreements the main conclusions and recommendations are made for further successful bilateral cooperation between the US and Russia in the Bering Strait region.